Domains of Acculturation and their Effects on Substance Use and Sexual Behavior in Recent Hispanic Immigrant Adolescents - Schwartz, Seth J. (2014)
This study evaluated the immigrant paradox by ascertaining the effects of multiple components of acculturation on substance use and sexual behavior among recently immigrated Hispanic adolescents primarily from Mexico (35%) and Cuba (31%). A sample of 302 adolescents (53% boys; mean age 14.51 years) from Miami (n = 152) and Los Angeles (n = 150) provided data on Hispanic and U.S. cultural practices, values, and identifications at baseline and provided reports of cigarette use, alcohol use, sexual activity, and unprotected sex approximately one year later. Results indicated strong gender differences, with the majority of significant findings emerging for boys. Supporting the immigrant paradox (i.e., that becoming oriented toward U.S. culture is predictive of increased health risks), individualist values predicted greater numbers of oral sex partners and unprotected sex occasions for boys. However, contrary to the immigrant paradox, for boys, both U.S. practices and U.S. identification predicted less heavy drinking, fewer oral and vaginal/anal sex partners, and less unprotected vaginal/anal sex. Ethnic identity (identification with one’s heritage culture) predicted greater numbers of sexual partners but negatively predicted unprotected sex. Results indicate a need for multidimensional, multi-domain models of acculturation and suggest that more work is needed to determine the most effective ways to culturally inform prevention programs.